Implementasi Strategi Pemasaran Pada UMKM Rumah Tenun Kota Tebing Tinggi - Liliace, Reni; Adam, Aisyah Azhar; Sitanggang, Seprina Ruleta; Fitriyani, Fitriyani (Community Service Progress, 2025)
This study analyzes the implementation of marketing strategies at the Rumah Tenun micro, small, and medium enterprise (MSME) in Tebing Tinggi City, which plays an important role in preserving local cultural heritage while supporting the community’s economy. Increasing market competition and shifts in consumer behavior demand more adaptive and innovative marketing strategies. Using a qualitative descriptive approach, this research examines the integration of traditional and digital marketing elements, including product strategy, pricing, promotion, and distribution. The findings indicate that combining traditional promotional methods with digital platforms enhances market reach, strengthens brand identity, and increases customer engagement. The study concludes that adopting hybrid marketing strategies is essential for sustaining the competitiveness and sustainability of Rumah Tenun MSMEs. Recommendations emphasize digital optimization, brand differentiation, and collaboration to enhance market performance.